The Planning of Learning Model for Students with Hearing Impairments in the Elementary School Inclusion - Indina Tarjiah (Department of Special Education, 2017)
This research aims to produce a design of the model of planning learning for students with hearing impairments in inclusive elementary school in the region of DKI Jakarta. This research involves a number of subjects as participants i.e. academics, teachers in inclusive elementary schools, and teachers of the school outstanding. Research methods used in this research is quantitative research with engineering survey to obtain data about problems in learning for deaf learners to then be processed, analyzed which then serve as material for the development of model design planning of learning for students with hearing impairments at Elementary School Inclusion. The research was carried out in February until May 2016 at 10 State primary school inclusive education providers in the region of DKI Jakarta. The results showed that of the 10 schools, there are 7 schools have yet to develop a plan of learning and not to apply the principles of learning for the students with hearing impairments, while the 3 schools have already begun trying to adjust to the needs of deaf students, although not optimal. Based on the above findings, then design learning planning model designed for deaf students with the following stages: (1) the development of the syllabus. (2) the development of the plan of implementation of the Programme of learning and Individual Learning.